KESETARAAN GENDER UNTUK PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA - Dudi Badruzaman; Yus Hermansyah; Irpan Helmi (Justitia et Pax, 2020)
Discrimination against women is a problem that often occurs in almost all levels of society, even in most parts of the world. This study aims to determine the understanding of gender equality and how the results of the analysis in order to reduce violence and provide justice for women in Indonesia. The method used is field research by collecting data, conducting interviews and analyzing documentation data. Gender is not a movement that fights for women's destiny, on the contrary, it is a movement that erases maternal instincts from women by separating the natural and non-natural roles. Thus, gender is not just a term but a doctrinfeminist that erases human nature.Discrimination against women is a problem that often occurs in almost all levels of society, even in most parts of the world. This study aims to determine the understanding of gender equality and how the results of the analysis in order to reduce violence and provide justice for women in Indonesia. The method used is field research by collecting data, conducting interviews and analyzing documentation data. Gender is not a movement that fights for women's destiny, on the contrary, it is a movement that erases maternal instincts from women by separating the natural and non-natural roles. Thus, gender is not just a term but a doctrinfeminist that erases human nature